The accounting reform in Spain. An analysis form the point of view of time and degree of knowledge of accountants - Esther Ortiz-Martínez (Revista Brasileira de Gestão de Negócios - RBGN, 2019)
Purpose – The goal of this paper is to prove if there is a change in the Spanish professionals´ perception about the accounting reform in Spain due to the adaptation to IFRS, depending on when it is analysed, and also if this opinion depends on their degree of knowledge. Design/methodology/approach – We have used a survey done to the Spanish accountants in different four times after the accounting reform.Findings – It is obtained that the degree of knowledge of accountants increases after the first application of the new requirements and it affects their opinion about the accounting reform. It is important to highlight that the perceptions are not the same about each different aspect of accounting areas.Originality/value – Accountants play an important role in the accounting development and so it is valuable to know their opinion after an accounting reform when trying to get comparability with IFRS. Their perceptions are less critical when they have got experience about the new rules and prefer changing the national regulation to requiring directly IFRS in order to get this comparability.